Identity and Relationships of Alterity Among Adolescents: Disquisitions About their Construction in the Digital Setting - Martín Martínez, Sandra Gisela (2024)
This essay presents a reflection about how adolescents create their identity and relations of alterity through their interaction experiences in a constant transit between physical and virtual spaces. Going to the Lévinas philosophical theory about alterity, it seeks to make an approximation to the understanding of the forms of encounter and relationship between youth in the online social networks sphere, which implies analyzing some specificities and scope of digital communication, as well as the construction of the digital self, using the image and social interaction. It is important to highlight that the relationship with the other in the digital setting has been studied as cyber coexistence, delving into the risks and possible solutions. However, in this text it is proposed to consider the relationship with others in the digital sphere, as a complex process that involves strangers and in which it is also possible to care of others, recognizing their differences, being supportive and empathetic. Nevertheless, it is important to point out that relationships of alterity are not always framed within an ideal of perfection and harmony.